BIDIRECTIONAL RELATION BETWEEN SPATIAL ADAPTATION AND INTERIORITY IN PERANAKAN BATIK LASEM-HOUSE - Nor Faricha, Asa
The 'Peranakan' houses, including those in Lasem, Central Java, Indonesia, are significant architectural heritage. Lasem, known for its batik heritage, is also called a 'Little China Town' due to its multiethnic and cultural significance. Unfortunately, many Peranakan houses in Lasem are poorly maintained or sold off. One of the few that still survives is the Peranakan Batik House. It has three identities: dwelling, productive, and Peranakan house, which shows spatial adaptation over time. The Chinese community’s tradition of bequeathing homes to descendants means the next generations hold a crucial role. They hold memories and aspirations related to the house and batik business, forming their 'interiority.' This research explores the bidirectional relationship between spatial adaptation and the interiority of the next generation in Peranakan batik houses, focusing on preserving cultural heritage. Through a qualitative narrative inquiry approach, the study collects data using in-depth interviews, observations, and photo documentation. Two batik houses in Lasem District are studied: Kidang Mas (7th generation owner) and Lumintu (6th generation owner). The findings show that these houses have undergone various spatial adaptations to meet the needs of the batik business, particularly in the front terrace, altar, and production area with the most physical elements that are ground, platform/raised area, and roof/canopy. Both owners share a deep interiority, valuing their ancestral heritage and appreciating their house's architectural style, leading to minimal yet essential changes. Each owner also has their dreams for their batik businesses. The research concludes that the bidirectional relationship happens through interiority that significantly influences spatial adaptation, with each reflecting and reinforcing the other. This relationship helps preserve cultural heritage, with non-physical interiority manifesting through the physical elements of the Peranakan batik houses.